Pasteurized Autograft-Prosthesis Composite Reconstruction May Not Be a Viable Primary Procedure for Large Skeletal Defects after Resection of Sarcoma - Lee, Seung Yong (Sarcoma, 2017)
BACKGROUND: Among various types of composite biological reconstruction, pasteurized autograft-prosthesis composite (PPC) is popular when allograft is unavailable. Previous limited cohort study indicated result comparable to tumor prosthesis. However, as case number and follow-up increase, we experienced more complications than anticipated. We questioned the usefulness of PPC as a viable reconstructive option. METHODS: We reviewed 142 PPCs and analyzed overall and location-related survival and factors associated with the failure of PPC. RESULTS: Twenty-year survival rate of 142 PPCs was 39.8 ± 10.0%. Fifty-two (36.6%) of 142 PPCs showed failure. Among various locations, the proximal femur showed best survival: 78.0 ± 9.9%. Final status of the 52 failed PPCs was modular tumor prosthesis in 23 (43%), arthrodesis in 11 (21%), pseudarthrosis in 7 (13%), amputation in 7 (13%), and allograft-prosthesis composite in 4 (8%). Tumor volume > 200 cc (p = 0.001), pasteurization length ≤ 10 cm (p = 0.002), male sex (p = 0.02), and locations in pelvis or tibia (p = 0.029) were poor prognostic factors. CONCLUSIONS: Long-term survival of PPCs was below expectations. Despite the complexity of the procedure, there is little survival gain over tumor prosthesis. PPC may be indicated when a modular prosthesis is not readily available.